FACTORS CONTRIBUTING TO INCREASED INDISPLINE INSECONDARY SCHOOL IN KENYA. - Ngok, Peter (Kabarak University, 2013)
However, as recent as 2008, schools were hit by a wave of unrests where over “300 secondary schools were hit by unrests that saw students disrupt learning, besides destroying property worth of millions of shillings” (Daily Nation, July 14, 2008). Events such as these and many others which go on undocumented show us how our schools are facing a great challenge. It seems that there is a big problem in our schools in terms of discipline.
Keywords: Increased indiscipline